Up‐regulation of β‐amyloidogenesis in neuron‐like human cells by both 24‐ and 27‐hydroxycholesterol: protective effect of N‐acetyl‐cysteine. Issue 3 (25th February 2014) - Gamba, Paola; Guglielmotto, Michela; Testa, Gabriella; Monteleone, Debora; Zerbinati, Chiara; Gargiulo, Simona; Biasi, Fiorella; Iuliano, Luigi; Giaccone, Giorgio; Mauro, Alessandro; Poli, Giuseppe; Tamagno, Elena; et al.
Summary An abnormal accumulation of cholesterol oxidation products in the brain of patients with Alzheimer's disease (AD) would further link an impaired cholesterol metabolism in the pathogenesis of the disease. The first evidence stemming from the content of oxysterols in autopsy samples from AD and normal brains points to an increase in both 27‐hydroxycholesterol (27‐OH) and 24‐hydroxycholesterol (24‐OH) in the frontal cortex of AD brains, with a trend that appears related to the disease severity. The challenge of differentiated SK‐N‐BE human neuroblastoma cells with patho‐physiologically relevant amounts of 27‐OH and 24‐OH showed that both oxysterols induce a net synthesis of Aβ1‐42 by up‐regulating expression levels of amyloid precursor protein and β‐secretase, as well as the β‐secretase activity. Interestingly, cell pretreatment with N‐acetyl‐cysteine (NAC) fully prevented the enhancement of β‐amyloidogenesis induced by the two oxysterols. The reported findings link an impaired cholesterol oxidative metabolism to an excessive β‐amyloidogenesis and point to NAC as an efficient inhibitor of oxysterols‐induced Aβ toxic peptide accumulation in the brain.